Peran Teknologi Dalam Meningkatkan Efisiensi Pelayanan Publik - Sri Rahma Yulanda; Farhan Ergi Aldino; Nadira Anvasha; Jumiati Jumiati; Boni Saputra (CV. ITTC INDONESIA, 2025)
In the current digital era, developments in information and communication technology have become a key factor in transforming the delivery of public services. With the application of technology in government administration systems, significant changes have occurred in terms of efficiency, accessibility, and transparency of services provided to the public. Various services, such as document registration, permit applications, and tax payments, can now be carried out online through online platforms and mobile applications, without the need to physically visit government offices. This helps reduce waiting times, minimize bureaucracy, and lower operational costs for both the government and the public. Additionally, the implementation of digital technologies such as e-government, e-budgeting, and e-reporting enhances accountability and facilitates direct audit and evaluation processes. Technology also facilitates access to public services in remote areas, reducing the gap in access between urban and rural regions. The relationship between the government and the public becomes more efficient, responsive, and interactive through social media, complaint applications, and online reporting systems. The application of data analysis and artificial intelligence also helps evidence-based decision-making, enabling the government to formulate more targeted policies according to the needs of society. However, digital transformation in public services also poses challenges, such as the need for adequate technological infrastructure, increased digital literacy among the public, and high-security systems to protect personal data. To achieve inclusive, efficient, and transparent public services, it is crucial for the government to have a commitment and sustainable investment.